STREET CHILDREN, POOR TOUCH EDUCATION & PUTTING ATTENTION - Mujahidil Mustaqim (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract The study wanted to explore how much physiological, psychological, family, school and community factors to the religiousity of street children in Padang City. This research was conducted in one of the schools that inaugurated the city of Padang as a special education school for urban children especially street children. This type of research is field research by using combination method (mixed method) with sequential explanatory design model type. This study yields the following conclusions: First, the results of quantitative research mention the physiological, psychological, family, school and community influence on the religiosity of learners respectively by 6.3%, 17.8%, 12.5%, 10.2% and 14.9%. This figure indicates that street children although already formalized education, but considered not have a significant impact on the religiosity of street children. The two qualitative research results describe that the low nominal influence is caused by the various problems of life faced by street children, among them the most dominant are the problems of family disharmony, such as the concern and the poor attention of the parent to the education of the child, the unhealthy family communication, parental divorce, misconduct of children, financial shortage and so on. This then causes poor street children from the values ​​of religiosity. The results of this study provide a clear picture that the street children are still not getting the proper education as children in the usual and massive attention that all circles.  Abstrak Penelitian ingin menelusuri seberapa besar faktor fisiologis, psikologis, keluarga, sekolah dan masyarakat terhadap religuisitas anak jalanan di Kota Padang.. Penelitian ini dilakukan di salah satu sekolah yang diresmikan Kota Padang sebagai sekolah pendidikan layanan khusus anak-anak urban perkotaan terutama anak jalanan. Jenis penelitian ini adalah penelitian lapangan dengan menggunakan metode kombinasi (mixed method) dengan jenis model sequential explanatory design. Penelitian ini menghasilkan sejumlah kesimpulan berikut: Pertama, hasil penelitian kuantitatif menyebutkan pengaruh fisiologis, psikologis, keluarga, sekolah dan masyarakat terhadap religiusitas peserta didik masing-masing sebesar 6.3%, 17.8%,  12.5%, 10.2% dan 14.9%. Angka ini menunjukkan bahwa anak jalanan meskipun sudah diformalitaskan pendidikannya, akan tetapi dinilai belum memberi dampak yang signifikan terhadap religiusitas anak jalanan. Kedua¸hasil penelitian kualitatif mendeskripsikan bahwa rendahnya nominal pengaruh disebabkan karena peliknya berbagai masalah kehidupan yang dihadapi anak jalanan, diantaranya yang paling dominan adalah masalah-masalah ketidakharmonisan keluarga, seperti kepedulian dan perhatian orangtua yang minim terhadap pendidikan anak, komunikasi keluarga yang tidak hangat, perselingkuhan, perceraian orangtua, salah pola asuh, kekurangan finansial dan sebagainya. Hal ini kemudian menyebabkan anak jalanan miskin dari nilai-nilai religiusitas. Hasil penelitian ini memberi gambaran nyata bahwa bahwa anak jalanan masih belum mendapatkan pendidikan yang layak sebagaimana anak-anak pada lazimnya dan perhatian yang massif yang semua kalangan.  How to Cite : Mustaqim, M. (2017).  Street Children, Poor Touch Education & Putting Attention. TARBIYA: Journal of Education in Muslim Society, 4(2), 200-215. doi:10.15408/tjems.v4i2.7232. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.7232